Deadly encounter - Mills, DiAnn (FBI task force, 2016)
Airport ranger volunteer Stacy Broussard expected a peaceful Saturday morning ride around the perimeter of Houston's airport. What she encounters instead is a brutal homicide and a baffling mystery. Next to the body is an injured dog, the dead man's motorcycle, and a drone armed with a laser capable of taking down a 747. Special agent Alex LeBlanc sees a clear-cut case of terrorism, but his past has taught him to be suspicious of everyone, even witnesses. But when Stacy's gruesome discovery is only the first in a string of incidents that throw her life into a tailspin, Alex begins to wonder if Stacy was targeted, so they must work together to prevent another deadly encounter.